Roles of circRNAs in viral pathogenesis - Liu, Jiayin; Wang, Yiming; Zheng, Meichun; Du, Jiayuan; Maarouf, Mohamed; Chen, Ji-Long (Frontiers in Cellular and Infection Microbiology, 2025)
Circular RNAs (circRNAs) are a class of non-coding RNAs with a covalently closed circular structure, lacking 5’-caps or 3’-poly(A) tails. They are relatively conserved, highly stable, and often exhibit tissue- or cell-specific production in eukaryotic cells. Based on the advances in sequencing technologies and bioinformatics, multiple reports have suggested that viruses and other microorganisms may encode circRNA-like molecules, providing new insights into the physiological and pathological roles of circRNAs. The innate immune system functions as the body’s primary defense mechanism against viral infections. It detects pathogen-associated molecular patterns (PAMPs) and activates signaling pathways to suppress viral replication and limit their spread. CircRNAs are involved in regulation of the host innate immune signaling pathways and play essential roles in viral pathogenesis. It has been shown that circRNAs can regulate gene expression by acting as miRNA sponges or protein sponges, or encoding small proteins in specific cases. For example, previous studies have revealed that circRNAs participate in the host antiviral immune response through the competitive endogenous RNA (ceRNA) network by acting as miRNA sponges. This review highlights research progress in the regulation and functions of host- and virus-encoded circRNAs in host-virus interactions, as well as their potential as diagnostic biomarkers and therapeutic targets in clinical applications.